Cyclooxygenases and Lipoxygenases in Cancer Drug Resistance - Hasan Hüseyin Kazan; Ahmet Çağlar Özketen; Çağrı Urfalı Mamatoğlu (Gazi Medical Journal)
Cancer drug resistance is a critical factor restricting the success rate of chemotherapeutics. Alterations in both cellular and systemic mechanisms could induce drug resistance in cancer. At the cellular level, numerous pathways have been associated with cancer drug resistance depending on the tumor origin and anti-cancer agent. Amongst other pathways including overexpression of multidrug resistance proteins, lipid modifier enzymes have also been linked to drug resistance in cancer via regulation of multidrug resistance protein levels, cell death mechanisms, and reactive lipid and oxygen species. Here the involvement of cyclooxygenases (COXs) and lipoxygenases (LOXs) as members of lipid modifier enzymes in cancer drug resistance should be emphasized. In this review, we summarize the studies examining the vital role of COXs/LOXs in the development and modulation of cancer drug resistance and cancer treatment.